Phenol degradation by heterogeneous fenton process - Cam, Nguyen Thi Dieu; Noi, Nguyen Van; Hang, Nguyen Thu; Phuong, Dao Thanh; Anh, Do Thi Ngoc; Chi, Nguyen Thi Phuong Le (Vietnam Journal of Chemistry, 2012)
The mixed Al-Fe pillared bentonite was tested as a heterogeneous catalyst for the photo-Fenton oxidation of phenol under solar light irradiation. The structural characteristics of the catalysts were examined by XRD and SEM. The results indicate that the heterogeneous photo-Fenton process employing the Al-Fe pillared bentonite as catalyst exhibits higher photo-catalytic activity compared to its corresponding homogeneous photo-Fenton process.